2016
DOI: 10.1016/j.healun.2016.01.1066
|View full text |Cite
|
Sign up to set email alerts
|

Massive Donor Transfusion Increases Recipient Early Mortality after Lung Transplantation

Abstract: transfusion were most commonly younger trauma patients. Following adjustment for confounding variables, massive transfusion was significantly associated with an increased risk in 30-day (OR = 1.41; CI 1.03, 1.92; p-value = .03) and 90-day mortality (OR = 1.36; CI 1.06, 1.73; p-value = .01) but not 1 year mortality (OR = 1.17; CI 0.97, 1.41; p-value = .11). There was no significant difference in length of stay or hospital free days with respect to donor transfusion. Conclusion: Massive donor blood transfusion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Interestingly, a retrospective review of the United Network of Organ Sharing database by Borders et al 23 in 2016 found that large-volume pRBC transfusion in the donor prior to lung donation was associated with increased early recipient mortality after transplantation. In this review of a total 16 255 donors, 8835 (54%) donors had received at least one RBC transfusion prior to organ procurement.…”
Section: Transfusion and Primary Graft Dysfunction/acute Lung Rejectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a retrospective review of the United Network of Organ Sharing database by Borders et al 23 in 2016 found that large-volume pRBC transfusion in the donor prior to lung donation was associated with increased early recipient mortality after transplantation. In this review of a total 16 255 donors, 8835 (54%) donors had received at least one RBC transfusion prior to organ procurement.…”
Section: Transfusion and Primary Graft Dysfunction/acute Lung Rejectionmentioning
confidence: 99%
“…Whether this observed increase in early mortality is secondary to PGD, TRALI, or another process is unclear as the diagnosis of PGD was not controlled for in this study, though PGD is believed to be likely given that it is the leading cause of early posttransplant mortality. 23 There are several proposed mechanisms to explain the association between blood product transfusion and subsequent development of PGD. The pathophysiology of PGD appears to be similar to other forms of acute lung injury, and biomarkers that are altered in other pulmonary disease states, acute respiratory distress syndrome, and TRALI are also altered in PGD.…”
Section: Transfusion and Primary Graft Dysfunction/acute Lung Rejectionmentioning
confidence: 99%